Peran Guru Bimbingan dan Konseling Dalam Mengatasi Kejenuhan Belajar Melalui Ice Breaking di SMP Negeri 2 Padang Panjang - Yani, Anisa Putri; Tanjung, Arif Irpan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine the role of Guidance and Counseling teachers in overcoming learning boredom through ice breaking at SMP Negeri 2 Padang Panjang. The research method used is qualitative. The results showed that the factors that cause students' learning saturation include a monotonous learning atmosphere, less interesting material, less varied teacher teaching methods, unfriendly teacher attitudes, and parents' demands for high scores. The role of counseling teachers in overcoming learning saturation by applying ice breaking has proven to be effective in making students excited about attending lessons again. Therefore, it is necessary to have good cooperation between counseling teachers and subject teachers to maximize counseling guidance services in order to reduce students' learning saturation.